The Influence of Attitude, Subjective Norms, and Perception of Control on Customers' Decisions to Use People's Business Credit Financing Products (KUR) with Religiosity as a Mediating Variable (Survey at Bank Syariah Indonesia (BSI) KCP Indralaya) - Iin Fitria; Maya Panorama; Rinol Sumantri; Peny Cahaya Azwari (Eastasouth Institute, 2026)
This research is motivated by the importance of understanding the factors that influence customers' decisions in using People's Business Credit (KUR) financing products at Bank Syariah Indonesia (BSI) KCP Indralaya. The decision to use financing products is influenced not only by economic aspects but also by psychological and social factors explained through the Theory of Planned Behavior (TPB), namely attitude, subjective norms, and perception of behavioral control. In addition, religiosity is seen as having a role in strengthening customers' decisions in choosing sharia-based financing products. This study aims to analyze the influence of attitude, subjective norms, and perception of control on customers' decisions to use People's Business Credit (KUR) financing products with religiosity as a mediating variable at Bank Syariah Indonesia KCP Indralaya. This research uses a quantitative approach with an explanatory research type. The population of the study is customers using KUR financing products at BSI KCP Indralaya. Data collection techniques were carried out using questionnaires with measurement scales developed based on the indicators of each research variable. Data were analyzed using statistical analysis to test the direct and indirect effects between variables through religiosity as a mediating variable. The results of the study indicate that only perceived control has a significant effect on customers' decisions to use Sharia KUR financing products, while attitude and subjective norms do not show a significant effect. Religiosity also has a significant effect on customer decisions and only mediates the relationship between perceived control and customer decisions. The findings of this study can serve as evaluation material for Bank Syariah Indonesia to strengthen product information, simplify administrative procedures, improve customer assistance, and expand access to sharia financing services.